Diversidade de visitantes florais e potenciais polinizadores de tomateiros (Solanum lycopersicum L.) em cultivos orgânicos e tradicionais - Santos, Aline Borba dos (2009)
Agriculture uses several options to increase and conservation of the yields. The tomato cultivation is a typically traditional and fragile crop in which is used many synthetic products that cause damages to both environment and human health. To minimize the use of these products some mechanisms are adopted such as pollination. The variety of pollinators depend on the flower structure, in the case of S. lycopersicum., as other solanaceaes, and it is need flower vibration for the pollen drop. This vibration and the exclusive production of pollen determine the type of visitant of tomato flowers. To aim knowing the pollinators of tomato flowers, the differences between traditional and organic cultivation and the associated vegetation, it was collected visitant insects between March and November 2008 in the municipality of Itabaiana and Areia Branca, Sergipe state. It was collected 327 insects belonging to five orders. The Hymenoptera Order was the dominant taxon in which effective pollinators through buzz pollination was observed. Other visitants were considered as non-effective because they did not perform the buzz vibration; some causes damages the flowers during food searching. Among hymenopterans it was found: Anthophoridae; Apidae; Chalcididae; Eumeninae; Formicidae; Scollidae; Sphecidae; Halictidae; Vespidae; Coleopteras: Chrysomelidae, Carabidae e Coccinelidae. Among the Diptera Order: Ascilidae, Bibionidae, Syrphidae, Muscidae e Tabanidae. The representant of the Lepidoptera Order: Licaenidae, Nymphalidae e Papilonidae. The insect families of the Orthoptera Order were: Romaleidae e Tettigonidae, and Hemiptera Order were: Pentatomidae, Scutelaridae e Coreidae. The associated surrounding vegetation was respectively characterized the planting of other species (mostly coriander) or gramineae in traditional and organic tomato crops. The abundance and diversity of insect visitants in organic crops was greater than the higher in traditional crops.